A high-efficiency mixotrophic photoelectroactive biofilm reactor (MPBR) for enhanced simultaneous removal of nutrients and antibiotics by integrating light intensity regulation and microbial extracellular electron extraction. (1st January 2023) - Yao, Xinyuan; Sun, Jian; Bai, Xiaoyan; Yuan, Yong; Zhang, Yaping; Xu, Yanbin; Huang, Guofu
Abstract: The performance of a mixotrophic photoelectroactive biofilm reactor (MPBR) was improved in order to achieve enhanced simultaneous removal of multiple aqueous pollutants and the production of valuable biomass. The MPBR was optimized by integrating the regulation of light intensity (3000, 8000 and 23000 lux) and microbial extracellular electron extraction (using an electrode at −0.3, 0 and 0.3 V). Results showed that the MPBR operated at a high light intensity (23000 lux) with a potential of −0.3 V (Coulomb efficiency (CE) of 9.65%) achieved maximum pollutant removal efficiencies, effectively removing 65% NH4 + -N, 95% PO4 3- -P and 52% sulfadiazine (SDZ) within 72 h, exhibiting an increase by 30%, 56% and 26% compared to an MPBR operated at the same light intensity but without an externally applied potential. The use of an electrode with an applied potential of −0.3V was most suitable for the extraction of photosynthetic electrons from the photoelectroactive biofilm, in which Rhodocyclaceae was highly enriched, effectively alleviating photoinhibition and thereby enhancing N, P assimilation and SDZ degradation under high light conditions. A maximum lipid content of 409.28 mg/g was obtained under low light intensity (3000 lux) conditions with an applied potential of 0.3 V (CE 9.08%), while a maximum protein content of 362.29 mg/g was obtained at a low light intensity (3000 lux) and 0 V (CE 10.71%). The selective enrichment of Chlorobium and the subsequent enhanced conversion of excess available carbon under low light and positive potential stimulation conditions, were responsible for the enhanced accumulation of proteins and lipids in biomass. Graphical abstract: Image 1 Highlights: Integrated light and extracellular electron regulation enhance biofilm performance. The highest removal rates for N, P and SDZ are found at high light intensity/-0.3V. Applied potential of −0.3V alleviates photoinhibition of biofilm at high light. Low light coupled with −0.3V promotes protein and lipid accumulation in biomass. Microbial diversity in biofilm varied with light intensity and applied potentials.